Incidence of Anomalous Coronary Arteries in Pakistani Population - Ather Mehmood; Rizwan Uppal; Hassan Saleem; Attiya Hameed Khan (University of Lahore, 2024)
Objective: To identify the origin of coronary arteries and detect its abnormalities. Methodology: This was a retrospective analysis comprising 1200 patients during the course of 2 years from May 2021 to a May 2023 who underwent for coronary CT angiogram to determine the coronary artery anomalies at the Islamabad Diagnostician center, with the collaboration of South East Hospital and Research Center, Islamabad. All the patients who were included in this study had a base line heart rate>65 bpm, and suffered from coronary artery disease and chest pain. They were advised to avoid smoking and coffee 12 hours before the procedure and also avoided eating solid food 4 hours prior to the procedure. Results: The patients' mean age was 49 years, mean heart rate 61.39±5.356 and mean creatinine level was 1.029±1.383. It also showed that 85.7% male and only 2% females were in records. Medical history showed that 64.3% patients were hypertensive, 50% diabetic, 92% patients had presented with shortness of breath, 85% with chest pain, 35.7% were smokers and 42.9% had positive family history of heart diseases. Angina grading score also known as the Canadian cardiovascular society (CCS) showed 50% patients with CCS I, 28.6% CCS II and 21.4% CCS III. Conclusion: Coronary CT angiography is a highly effective diagnostic technique for the diagnosis and origin of coronary arteries as well as its course and termination. We can observe easily all the presentation which cannot be detected through other diagnostic tools.